A phase 2a randomized, double‐blind, placebo‐controlled, sequential dose‐escalation study to evaluate the efficacy and safety of ASP015K, a novel Janus kinase inhibitor, in patients with moderate‐to‐severe psoriasis. (1st September 2015) - Papp, K.; Pariser, D.; Catlin, M.; Wierz, G.; Ball, G.; Akinlade, B.; Zeiher, B.; Krueger, J.G.
Summary: Background: Many immune‐mediated disorders, including psoriasis, involve cytokine signalling via Janus kinase (JAK) enzymes. ASP015K (also designated JNJ‐54781532), a novel oral JAK inhibitor, has shown moderate selectivity for JAK3 over JAK1 and JAK2 in enzyme assays. Objectives: The objective of this study was to evaluate the efficacy and safety of escalating, sequentially grouped, doses of ASP015K vs. placebo in patients with moderate‐to‐severe psoriasis. Methods: This phase 2a multicentre, double‐blind, randomized, placebo‐controlled study (NCT01096862) enrolled 124 patients with moderate‐to‐severe plaque psoriasis. Five sequential ASP015K cohorts were enrolled, consisting of four twice‐daily dosing groups (10, 25, 60, 100 mg) and one once‐daily dosing group (50 mg) for 6 weeks. Results: The primary efficacy end point [mean change in Psoriasis Area and Severity Index score from baseline to end of treatment (EOT; day 42)] significantly favoured ASP015K (overall treatment effect; P < 0·001) vs. placebo, with greater improvements at higher doses. By EOT, the secondary end points [Physician Static Global Assessment (PSGA) score, percentage of patients achieving PSGA success, and change in percentage, body surface area (BSA)] also improved with ASP015K vs. placebo ( P < 0·001 for PSGA score and BSA; P < 0·01 for PSGA success). Epidermal thickness and proliferation decreased from baseline with ASP015K vs. placebo. ASP015K was generally well tolerated, with no serious adverse events (AEs) reported. Conclusions: In patients with moderate‐to‐severe psoriasis, ASP015K demonstrated dose‐dependent improvements in clinical and histological measures of severity over 6 weeks of treatment. At all doses, ASP015K was well tolerated, with no reported serious AEs.